2016
DOI: 10.3892/ijmm.2016.2469
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the WWOX gene on the regulation of biological processes during endometrial carcinogenesis

Abstract: The purpose of the present study was to investigate the role of WW domain containing oxidoreductase (WWOX) downregulation in biological cancer-related processes in normal (non-malignant) and cancer endometrial cell lines. We created an in vitro model using the normal endometrial cell line, THESC, and 2 endometrial cancer cell lines with varying degrees of differentiation, the Ishikawa (well-differentiated) and the MFE296 (moderately differentiated) cells, in which the WWOX tumor suppressor gene was silenced us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…In few cases, a synergistic effect was required between WWOX and AP-2α to demonstrate the adhesiveness reduction. The example of endometrial carcinoma revealed that integrin β4 and α2 are upregulated after WWOX silencing [62], suggesting that WWOX may regulate adhesion to laminin and collagens, respectively [63]. This is in line with another study on BLCA, where WWOX silencing increased adhesion to collagen IV [47].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In few cases, a synergistic effect was required between WWOX and AP-2α to demonstrate the adhesiveness reduction. The example of endometrial carcinoma revealed that integrin β4 and α2 are upregulated after WWOX silencing [62], suggesting that WWOX may regulate adhesion to laminin and collagens, respectively [63]. This is in line with another study on BLCA, where WWOX silencing increased adhesion to collagen IV [47].…”
Section: Discussionsupporting
confidence: 82%
“…Many pathways appeared in at least three comparisons; MAPK, TGFβ, WNT, NOTCH or ERBB signaling were found to be dependent on WWOX, AP-2α and AP-2γ, i.e., MAPK [78][79][80], TGFβ [80][81][82], WNT [83,84], NOTCH [85][86][87] and ERBB [88,89]. Since WWOX is considered a global gene expression modulator [62] and both AP-2 transcription factors regulate thousands of genes and biological processes via specific pathways [79], it was foreseeable that changes in their expression affect cellular events at the broad scale. CAGE data were filtered to indicate the most frequent DEGs; these genes were also screened as putative AP-2 targets.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining comparisons indicated that adhesion to collagen IV and laminin I was reduced during overexpression of WWOX and AP-2α or WWOX and AP-2γ (W/A or W/C, respectively). A previous study from our department identified that after WWOX silencing, an increase in the expression of integrin α2 and β4 in MFE-296 endometrial cancer cell line was observed ( 19 ), thus indicating the possibility of regulating adhesion to collagen and laminin, respectively ( 58 ). To the best of our knowledge, there are no scientific reports analyzing changes in the integrin profile regarding AP-2α/γ, while with the use of ELIXIR-approved ( 59 ) Integrated System for Motif Activity Response Analysis (ISMARA) tool ( 60 ), it was possible to confirm that the α2 integrin-encoding gene is in the top 200 AP-2α targets (based on the deposited project “ Inflammatory response time course, HUVEC (Inoue, 2006) ”; dataset3_v2; ZNF711_TFAP2A_TFAP2D), and both α2 and β4 integrin-encoding genes in the top 200 AP-2γ targets (based on the deposited project “ ENCODE cell lines, expression (Ernst 2011) ”; dataset6.1_ENCODE_expression_v2; TFAP2C).…”
Section: Discussionmentioning
confidence: 94%
“…Assays of colony formation, wound healing and 3D culture growth were performed to systematize function of each cellular variant in terms of self-renewal capacity, cell motility or ability to form tumorspheres, respectively. For instance, WWOX has become involved in the regulation of colony formation ( 19 ), as has AP-2α ( 30 ). In turn, AP-2γ has been associated with cell motility ( 25 ) as well as stemness and chemoresistance ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation